ТРИЗ-технологии в методике преподавания учебной дисциплины «Материаловедение» - Guseva T. A. (Relevant lines of scientific research: development prospects, 2017)
TRIZ-pedagogy focused on the formation of the factor of safety theoretical and practical knowledge in materials science from the College students who have, in the future, systemic thinking and creative individuality when solving complex problems in various fields of activity.
Keywords: учебная дисциплина; системный оператор; science; метод моделирования; материаловедение; ТРИЗ-педагогика; ТРИЗ-технологии; the discipline; TRIZ-pedagogics; TRIZ technology system operator; a method of modeling little creatures; маленькие человечки